Cold‐water coral Madrepora oculata in the eastern Ligurian Sea (NW Mediterranean): Historical and recent findings. Issue 5 (16th March 2017) - Fanelli, Emanuela; Delbono, Ivana; Ivaldi, Roberta; Pratellesi, Marta; Cocito, Silvia; Peirano, Andrea
Abstract: Cold‐water coral (CWC) ecosystems are long‐lived, slow‐growing and fragile, which makes them especially vulnerable to physical damage. In recent decades, CWCs have been severely threatened by fisheries, hydrocarbon extraction, pollution and other human activities. In the Mediterranean Sea, some investigations have been carried out on CWC ecosystems, mostly focused on their distributions within the central and eastern basins. Historical reports and fishermen's maps for the eastern Ligurian Sea (NW Mediterranean) from the 1960s document the occurrence of extensive banks of living CWC, mostly Madrepora oculata, between depths of 200 and 500 m. In 2013/2014, multibeam, side scan sonar (SSS) and remotely operated vehicle (ROV) surveys were carried out in that area, specifically in the Levante Canyon, to assess the occurrence, distribution and conservation status of CWC. The SSS and ROV showed numerous trawl tracks and small (10 cm high), dead, buried colonies at 300–500 m. Deeper, between 525 and 575 m, dense populations of living, 1 m high colonies of Madrepora oculata were found on the flanks of Levante Canyon. The deep sites showed colonies overturned or entangled by long‐line fishing activities. The discovery of new CWC banks not yet heavily damaged by fishing activities, suggests that urgent measures for conservation should be taken in the Mediterranean and worldwide. The present limitation of trawl‐fishing to above 1000 m depth, established by the General Fisheries Commission for the Mediterranean (GFCM) in 2005, seems to be ineffective, since CWCs are mostly located at less than 1000 m depth in the Ligurian Sea. A network of high‐seas/deep‐sea marine protected areas (MPAs) would favour a better strategy for protecting substantial areas of CWCs.